Stability Formulation Of Mouthwash From Sapodilla Fruit Extract (Manilkara Zapota) As Antibacterial Preventing Dental Caries - Nur Endah, Srie Rezeki; Suhardiana, Eddy; Roesman, Kamiel (Universitas Islam Lamongan, 2020)
Sapodilla fruit (Manilkara zapota) which is often used by the community as an antibacterial drug is part of the sapodilla plant. Sapodilla contains saponin, tannin, and flavonoid compounds which can be as antibacterial so it is suspected to be able to inhibit the growth of bacteria that cause dental caries. The purpose of this study was the Evaluation of Sawo Extract Mouthwash Formulation as an Antibacterial. The sample used was sapodilla fruit which had been extracted using the infusion method. The formulation of sapodilla fruit extract mouthwash was evaluated with the extract concentration of sapodilla fruit (Manilkara zapota) 1%, 5% and 10%. The results of this study obtained the most stable formulation with a concentration of extract of sapodilla fruit (Manilkara zapota) 1%.Â Â